Peningkatan Kompetensi Guru melalui Pelatihan Google Workspace dalam Pembelajaran Digital - Tati Suprapti; Umi Hayati; Abdul Hakim; Abdul Mukhyidin (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The development of information and communication technology (ICT) requires the world of education to adapt, especially in the learning process. Teachers as the frontline in education must have competence in utilizing ICT, one of which is through the use of Google Workspace. This study aims to improve teachers' competence in utilizing Google Workspace through training activities. The method used is training with a participatory approach and hands-on practice. This activity was carried out in the form of workshops attended by teachers from various levels of education, focusing on the utilization of Google applications such as Google Classroom, Google Drive, Google Docs, and Google Meet. The results of the activity show an increase in teachers' understanding and skills in operating Google Workspace, which has an impact on increasing the effectiveness of online and offline learning. This training also encourages teachers to be more creative in preparing teaching materials, managing digital classes, and building better interactions with students. The conclusion of this activity is that training on the use of Google Workspace is effective in improving teacher competence in the use of learning technology. It is expected that similar activities can be carried out in a sustainable manner to support digital transformation in education.